Crime scene prevention: a study of effective security management at International Islamic University Malaysia (IIUM) - Nil, Abdul Karnaen; Mohd Ali, Hairuddin (IIUM Press, 2011)
It is a short study conducted in IIUM that was trying to investigate what were the factors affected the crime scenes in IIUM mahallahs. There were five research questions to be focused on. Implications and recommendation for future research were also presented.